Pengaruh Insentif Terhadap Kinerja Karyawan Pada Hotel Mexsicana Kota Jambi - Said Almaududi; Muhammad Syukri; Camelia Puji Astuti (Universitas Batanghari, 2021)
The purpose of this study is to find out and describe the Incentives and Employee Performance at the Jambi City Mexsicana Hotel, and to determine the effect of the Incentives on the Employee Performance at the Jambi City Mexsicana Hotel. The type of data needed and collected in this study is quantitative data. The object of this study is the employee of the Mexsicana Hotel Jambi City. Sources of data in this study were employees of the City of Mexsicana Hotel Jambi taken through interviews by distributing questionnaires, data, and information obtained analyzed descriptively, to analyze employee responses to incentives for performance using a 5-choice scale. Based on the results of the regression analysis it was concluded that the regression equation Y = 32.316 + 0.154X + e. The correlation coefficient (R) of the independent variable is 0.767. This value indicates that the incentive relationship on Mexsicana Hotel Jambi Erat employees' performance is 0.767. While the coefficient of determination (R2) of 0.589 it means that the variation of change in Y is influenced by changes in X by 58.9%. So the magnitude of the effect of incentives on the performance of employees of the City of Mexsicana Hotel Jambi is 58.9% while the remaining 41.1% is influenced by other factors outside this study. Partially, there is an effect of incentives on the performance of Mexicicana Hotel Jambi City employees. This is indicated by the value of incentive thitung of 2.171 and ttable of 2.034 from the comparison results it can be seen that tcount is greater than ttable (thitung> ttable). Then H0 is rejected and Ha is accepted. By comparing the magnitude of the level of significance (sig) of research with a significant level of 0.05 then 0.002 <0.05 so that it can be said that there is a significant effect between incentives on the performance of employees of Mexsicana Hotel Jambi City. For the management of the City of Mexsicana Hotel Jambi, it is hoped that incentives can be noticed and increased in terms of employee performance. So that incentives for employee performance can be better in the future. Next researchers are expected to be able to conduct research using different variables from the variables studied.